A Multi-Center, Qualitative Assessment of Pediatrician and Maternal Perspectives on Rotavirus Vaccines and the Detection of Porcine circovirus - Locke David; Albertin Christina; Kobayashi Ana; Klein Eileen J; Downing Kimberly; Wikswo Mary; Opel Douglas; Kennedy Allison; Humiston Sharon; Payne Daniel C; Chesley Claudia; Staat Mary A (BMC, 2011)
Abstract Background In 2010, researchers using novel laboratory techniques found that US-licensed rotavirus vaccines contain DNA or DNA fragments from Porcine circovirus (PCV), a virus common among pigs but not believed to cause illness in humans. We sought to understand pediatricians' and mothers' perspectives on this finding. Methods We conducted three iterations of focus groups for pediatricians and non-vaccine hesitant mothers in Seattle, WA, Cincinnati, OH, and Rochester, NY. Focus groups explored perceptions of rotavirus disease, rotavirus vaccination, and attitudes about the detection of PCV material in rotavirus vaccines. Results Pediatricians understood firsthand the success of rotavirus vaccines in preventing severe acute gastroenteritis among infants and young children. They measured this benefit against the theoretical risk of DNA material from PCV in rotavirus vaccines, determining overall that the PCV finding was of no clinical significance. Particularly influential was the realization that the large, randomized clinical trials that found both vaccines to be highly effective and safe were conducted with DNA material from PCV already in the vaccines. Most mothers supported the ideal of full disclosure regarding vaccination risks and benefits. However, with a scientific topic of this complexity, simplified information regarding PCV material in rotavirus vaccines seemed frightening and suspicious, and detailed information was frequently overwhelming. Mothers often remarked that if they did not understand a medical or technical topic regarding their child's health, they relied on their pediatrician's guidance. Many mothers and pediatricians were also concerned that persons who abstain from pork consumption for religious or personal reasons may have unsubstantiated fears of the PCV finding. Conclusions Pediatricians considered the detection of DNA material from PCV in rotavirus vaccines a "non-issue" and reported little hesitation in continuing to recommend the vaccines. Mothers desired transparency, but ultimately trusted their pediatrician's recommendation. Both vaccines are currently approved for their intended use, and no risk of human PCV illness has been reported. Communicating this topic to pediatricians and mothers requires sensitivity to a broad range of technical understanding and personal concerns.